Assessing the impact of lifestyle and basic necessity price inflation on welfare through the lens of Islamic perspective - Nur, Melani Azzahra; Sudiarti, Sri; Batubara, Chuzaimah (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2025)
This research investigates the impact of lifestyle choices and the rising prices of necessities on community welfare. The study employs a probability sampling technique using primary data collected through questionnaires with a sample size of 100 participants. The analysis is conducted using Structural Equation Modeling (SEM) facilitated by SmartPLS version 4, which aids in addressing the formulated research questions and hypotheses while examining the relationships between the variables. The findings indicate that lifestyle does not significantly influence community welfare. In contrast, the increase in prices of necessities is found to have a substantial effect on the welfare of the community. Public interest statements The article will provide valuable insights into applying a holistic approach to offer a competitive advantage and ensure the organization is well-positioned to thrive and innovate in an increasingly complex world.